The Influence of Work Discipline, Work Environment and Organizational Culture on Teacher Performance at SMP Negeri 252 Jakarta with Work Motivation as a Mediating Variable - Cintya Puput Zulaida; Parwoto Parwoto (Journal of Social Research, 2023)
In educational institutions, the quality and quantity of teachers can be seen from their performance. Factors that can affect performance come from factors within a person as well as external factors. This study aims to determine the Influence of Work Discipline, Work Environment, and Organizational Culture on Teacher Performance at SMP Negeri 252 Jakarta with Work Motivation as a Mediation variable. The population in this study amounted to 57 people with a total sample of 57 people, sampling using saturated samples. Data analysis method using SEM-PLS Version 3. The results of this study showed that in direct influence, work discipline, work environment, organizational culture and work motivation partially had a positive effect of seventy-two point four percent on teacher performance. The dominant factor influencing teacher performance is motivation with dimensions of social needs. Then in the direct influence of work discipline, work environment and organizational culture partially have a positive effect of sixty-two point four percent on work motivation. Factors that influence work motivation are an organizational culture with dimensions of how to face challenges. In indirect influence, work motivation does not mediate work discipline on teacher performance, but work motivation fully mediates the work environment on teacher performance and work motivation partially mediates organizational culture.